Quando o imprevisto bate à porta: atuação do enfermeiro no atendimento à demanda espontânea na estratégia saúde da família - Felix, Gisele Barreto [UNIFESP] (2016)
The Family Health Strategy, which is the official policy of primary health care in Brazil, was created as an attempt to implement the principles and guidelines of the Brazilian Health System. It is the point of preferential access to the system, and, therefore, must be prepared to respond to the health needs of every day users presented to workers. It works with the programmed monitoring of the enrolled population, but it must also have the “door open” to accept what cannot be programmed: eventualities and the spontaneous demand. This study aimed to understand the nurses' work to care in the spontaneous demand in the Family Health Strategy. It is a case study which was built through a qualitative approach. The unit of analysis are 17 nurses working in 17 primary care health centers of the administrative district Jardim Angela, in São Paulo. The 17 semi-structured interviews were conducted in May 2014. The results describe the organization of spontaneous demand care in the health centers and how nurses, identified as mainly responsible, are organized and act on it. The difficulties faced, the resolution and the sources of pleasure/pain are determined by the significance of the activity for the professional. The relationship with the user is marked by disagreements and frustration which often are not possible to give answers according to the need and expectation of it. However, there are attitudes and circumstances that can make this delightful meeting and a source of motivation. Despite the lack of reflection on their practice in care to the spontaneous demand, nurses believe that it expresses the portray of professional “handyman”, and he is the most qualified professional in the service. Facilities, difficulties and opportunities for improvement in spontaneous demand care were listed. The resolution, humanization and the encounter with the user were addressed in greater depth in Chapter discussion. This study allowed us to understand through the nurse look how to act in care to the spontaneous demand in the Family Health Strategy. The challenge of being in a place that theoretically has the responsibility to accept all complaints from users, to develop appropriate responses and provide comprehensive care to the individual, without the guarantee of the necessary requirements to do so. We advocate the importance of placing the care of life in the center of production of health care to achieve the desired transformations. We show the existence of nurses in the system capable doors and committed to their work, but they can contribute more to the strengthening of the Brazilian Health System SUS. A system that works not just for a few characters, but for all actors, where the worker's appreciation is also a priority.